1980
DOI: 10.1136/bjo.64.6.392
|View full text |Cite
|
Sign up to set email alerts
|

Organised macular plaques in exudative diabetic maculopathy.

Abstract: SUMMARY Plaques of hard exudate measuring 0-5 to 10 disc diameters, which occurred in 5 eyes of 4 patients with diabetic maculopathy, showed complete organisation in 8 to 18 months with the formation of scars measuring 0-2 to 0 5 disc diameters. Spontaneous progression and regression of hard exudate in diabetic maculopathy was described by King et al.1 and Dobree,2 who found that plaque formation required years for resolution and was not followed by visual recovery. In a previous report3 we described the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Previous studies of patients with diabetic maculopathy have shown that hard exudates persisting over time tend to have a deleterious effect on visual acuity and may even lead to the formation of foveal scars [9,16]. These studies have either assessed the severity of hard exudates semi-quantitatively or the retinal area covered by hard exudate has been estimated with the disc area as reference; hence, precise measurements of changes in the hard exudate area have not been obtained.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies of patients with diabetic maculopathy have shown that hard exudates persisting over time tend to have a deleterious effect on visual acuity and may even lead to the formation of foveal scars [9,16]. These studies have either assessed the severity of hard exudates semi-quantitatively or the retinal area covered by hard exudate has been estimated with the disc area as reference; hence, precise measurements of changes in the hard exudate area have not been obtained.…”
Section: Discussionmentioning
confidence: 98%
“…HDL cholesterol was unrelated to the severity of any diabetic le sions in this study. Hard exudates consist of glyco-and li poprotein, phospholipid and fatty acids [14]. The usual model in the pathogenesis of hard exudates is an extravasa tion of intravascular components due to focal leakages from microaneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…18 Clinical features include enlarged foveal avascular zone, which is normally 300-500 microns and this is indicated by the presence of increased capillary dropouts on FFA. 19 , thread-like arteries and large retinal haemorrhages.…”
Section: Macular Ischaemiamentioning
confidence: 99%